2019
DOI: 10.5114/aoms.2019.89969
|View full text |Cite
|
Sign up to set email alerts
|

miR-200a-3p predicts prognosis and inhibits bladder cancer cell proliferation by targeting STAT4

Abstract: Introduction: STAT4 is a transcriptional regulator that has been reported to have oncogenic activities in various cancers. In our study, the posttranscriptional regulatory effect of miR-200a-3p on STAT4 and the prognostic significance of miR-200a-3p and STAT4 were evaluated in bladder cancer (BCa). Material and methods: Proliferation and apoptosis of BCa cell lines were monitored using CCK-8 and Annexin V-FITC assays, respectively. Gene and protein expression levels in BCa tissues and cells were detected using… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 34 publications
0
4
0
Order By: Relevance
“…Decreased STAT4-induced proliferation inhibition and apoptosis in sw780 and T24 cells, however, co-transfection of mir-200a-3p mimics and STAT4 reversed this effect. 36 In contrast, STAT4 showed the tumor suppressor effect in hepatocellular carcinoma (HCC) and was significantly correlated with Ki67 expression, histological grade, HBV infection, and tumor size in HCC clinical cohort. 37 Here, we revealed the prognostic value of STAT4 in clinical cohorts of breast cancer and demonstrated the oncogenic role of STAT4 in breast cancer BT549 cells.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Decreased STAT4-induced proliferation inhibition and apoptosis in sw780 and T24 cells, however, co-transfection of mir-200a-3p mimics and STAT4 reversed this effect. 36 In contrast, STAT4 showed the tumor suppressor effect in hepatocellular carcinoma (HCC) and was significantly correlated with Ki67 expression, histological grade, HBV infection, and tumor size in HCC clinical cohort. 37 Here, we revealed the prognostic value of STAT4 in clinical cohorts of breast cancer and demonstrated the oncogenic role of STAT4 in breast cancer BT549 cells.…”
Section: Discussionmentioning
confidence: 99%
“…Similar results have been reported in bladder cancer, where the expression of STAT4 in cancerous tissues was higher than that in adjacent non‐cancerous tissues at both the protein and mRNA level. Decreased STAT4‐induced proliferation inhibition and apoptosis in sw780 and T24 cells, however, co‐transfection of mir‐200a‐3p mimics and STAT4 reversed this effect 36 . In contrast, STAT4 showed the tumor suppressor effect in hepatocellular carcinoma (HCC) and was significantly correlated with Ki67 expression, histological grade, HBV infection, and tumor size in HCC clinical cohort 37 …”
Section: Discussionmentioning
confidence: 99%
“…Cell apoptosis and inflammation are the end results of oxidative stress causing fibrosis, cardiac injury and in extreme conditions heart failure [25][26][27]. A number of studies have suggested that miR-200a halts apoptosis in various cancer conditions [28,29]. Also miR-200a has been reported to downregulate mediators of inflammation such as IL-1 and TNF-α and also suppress the levels of HMGB1 [13].…”
Section: Discussionmentioning
confidence: 99%
“…Similarly, other signaling pathways regulating cell proliferation are targeted by miRNAs. MiR-200a binds STAT4 in bladder and liver cancer and decreases cell proliferation in vitro ( 162 , 218 ). In esophageal carcinoma, however, miR-200a acts as oncomiR and targets APC, an inhibitor of β-Catenin/Wnt signaling ( 70 ).…”
Section: Regulation Of Cell Proliferation By Mir-200 Familymentioning
confidence: 99%